Faktor Individu Terjadinya Kelelahan Kerja Pada Operator Alat Berat - Septyanda, Bagas; Lestari, Putri Winda (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2021)
Fatigue at work contributes more than 60% of the incidence of work accidents in the workplace. Initial observations showed that as many as 60% of heavy equipment operators experience work fatigue. The purpose of this study was to determine the individual factors of work fatigue on heavy equipment operators. Research design was cross-sectional. The research was conducted from April-May 2019 at the Thamrin Nine Project Jakarta. The population was 34 heavy equipment operators the sampling technique was total sampling. The instrument used was a Subjective Symptoms Test Questionnaire by Industrial Fatigue Research Committee. Data were analyzed by univariate and bivariate with chi-square statistical test. Based on the results of statistical tests, individual factors of work fatigue on heavy equipment operators were respondent age (p=0.023), health status (p=0.007), and nutritional status (p=0.034). Meanwhile, the behavior of consuming energy drinks was not related to work fatigue (p=0.227). The conclusion of this study is age, health status and nutritional status are individual factors in the occurrence of work fatigue in heavy equipment operators. Keywords : Individual Factors, Work Fatigue, Age, Nutritional Status, Health Status